2011
DOI: 10.3109/13693786.2010.495139
|View full text |Cite
|
Sign up to set email alerts
|

Implications of hypoxic microenvironments during invasive aspergillosis

Abstract: Summary In order to cause disease, all pathogens must tolerate microenvironmental stresses encountered in vivo during infection. One microenvironmental stress that is known to occur at sites of tissue damage is hypoxia. Yet, the occurrence and impact of hypoxic microenvironments during invasive aspergillosis, caused by the mold Aspergillus fumigatus, are essentially unknown. Here, we briefly review the potential implications of hypoxic microenvironments on the Aspergillus – host interaction. We focus on three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…Although a number of antifungals are available with excellent in vitro activity against A. fumigatus, their efficacy in vivo has been suboptimal. One contributing factor to this observation is that necrotic tissue surrounding pulmonary fungal lesions serves as a barrier to antifungal penetration, limiting the efficacy of these agents (7,8,168).…”
Section: Chapter 3 General Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a number of antifungals are available with excellent in vitro activity against A. fumigatus, their efficacy in vivo has been suboptimal. One contributing factor to this observation is that necrotic tissue surrounding pulmonary fungal lesions serves as a barrier to antifungal penetration, limiting the efficacy of these agents (7,8,168).…”
Section: Chapter 3 General Discussion and Conclusionmentioning
confidence: 99%
“…The hallmark pathophysiological features of established IPA such as tissue infarction, vascular coagulation, and necrosis that create a favourable microenvironment for the invading fungus, can also serve as a barrier to antifungal penetration. Impaired penetration of antifungal agents at the site of infection may explain treatment failure when dealing with fungi that are susceptible to the antifungal agent being administered (6)(7)(8). This hypothesis is supported by studies of intrapulmonary amphotericin B levels in a patient with IPA.…”
Section: Intrapulmonary Pharmacokinetics In Ipamentioning
confidence: 94%
See 2 more Smart Citations
“…It has been shown that inflammation of the lung causes extensive tissue destruction that leads to hypoxic conditions (51,52). In addition, hypoxia can alter the efficacy of antifungal drugs on Aspergillus, causing an increase in the inhibition by amphotericin B, micafungin, and anidulafungin, a slight decrease in the efficacy of itraconazole, and no effect on voriconazole (53). The effectiveness of azoles is reduced under hypoxic conditions due to the reduction in ergosterol biosynthesis, which is one of the pathways more dependent on partial O 2 pressure (pO 2 ).…”
Section: Figmentioning
confidence: 99%